Cutis verticis gyrata : An interesting cutaneous finding in acromegaly - Tripathi, M; Mukherjee, K K (Nepal Journal of Dermatology, Venereology & Leprology, 2016)
Not available (Letter to Editor) NJDVL Vol. 13, No. 1, 2015 Page : 73-74